(untitled) (AYUSHDHARA, 2017)
Management of chronic wound becomes difficult when it overlays by recurrent infection, peripheral tissue oedema or slough/necrotized tissues. Wound debridement provides healthy environment by removing of unhealthy tissues. In practice of Ayurveda, many of herbs or herbo-mineral formulations are being used for wound care. Dhanvayas, also known as Dhamaso, is an under shrub belongs to Zygophyllaceae family. Traditionally it is being used in fever, hepatitis, boil, skin eruption, tumours and as blood purifier. Animal experimental studies also proves its wound healing properties. Here a case of chronic wound on left lower limb over anterior aspect of the tibia associated with recurrent cellulitis, serous discharge and itching; attended the OPD of Shalya Tantra Department of IPGT&RA, Jamnagar. On measurement it was 8 cm x 4 cm sized. After taking proper history, clinical examination and necessary investigations this case was successfully treated with local application of Dhanvayas (Fagonia cretica Linn.) powder as paste. Wound was daily cleaned with Dhanvayas kwatha (Decoction) and then paste was applied over the lesions in the morning and continued till healing of wound. Assessment was done in regular interval. Itching followed by discharge was reduced remarkably within week. Wound was healed completely within six weeks without any complication which showed wound healing activity of Dhanvayas powder.